Study of thrombocytopenia in pregnancy: clinical presentation and outcome at tertiary care rural institute - Singh, Jigyasa; Kumari, Kalpana; Verma, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Platelet count below 1.5 lakh/cumm is called as thrombocytopenia. After anaemia it is the second most common haematological disorder in pregnancy. It affects nearly 6 to 15%; on an average 10% of all pregnancies. Gestational thrombocytopenia is a clinically benign thrombocytopenic disorder usually occurring in late pregnancy. It resolves spontaneously after delivery. Methods: It is a hospital based prospective observational study over a period of 1 year. All pregnant women who attended OPD at the department of obstetrics and gynecology, UPUMS, Saifai for antenatal checkup were included for the study and blood sample was withdrawn. Results: Out of 263 cases enrolled for study, 90 women were found to have thrombocytopenia, and 173 had normal platelet count. Thus, incidence of thrombocytopenia was 34%. Gestational thrombocytopenia accounted for majority of cases of thrombocytopenia in pregnancy (50%) followed by hypertensive disorders (22.4%). It was further followed by ITP (11.11%) and dengue (5.5%). Conclusions: Gestational thrombocytopenia is the most common cause of thrombocytopenia during pregnancy (50%), but other underlying causes must be considered as well. A thorough history and physical examination will rule out most causes.